The Role of Photoactivated and Non-Photoactivated Verteporfin on Tumor - Changran Wei; Xiangqi Li; Xiangqi Li (Frontiers Media S.A., 2020)
Verteporfin (VP) has long been clinically used to treat age-related macular degeneration (AMD) through photodynamic therapy (PDT). Recent studies have reported a significant anti-tumor effect of VP as well. Yes-associated protein (YAP) is a pro-tumorigenic factor that is aberrantly expressed in various cancers and is a central effector of the Hippo signaling pathway that regulates organ size and tumorigenesis. VP can inhibit YAP without photoactivation, along with suppressing autophagy, and downregulating germinal center kinase-like kinase (GLK) and STE20/SPS1-related proline/alanine-rich kinase (SPAK). In addition, VP can induce mitochondrial damage and increase the production of reactive oxygen species (ROS) upon photoactivation, and is an effective photosensitizer (PS) in anti-tumor PDT. We have reviewed the direct and adjuvant therapeutic action of VP as a PS, and its YAP/TEA domain (TEAD)-dependent and independent pharmacological effects in the absence of light activation against cancer cells and solid tumors. Based on the present evidence, VP may be repositioned as a promising anti-cancer chemotherapeutic and adjuvant drug.